Factors influence on perceived academic stress among sports student during online learning / Siti Nur Dianah Ahmad Jani and Wahidah Tumijan - Ahmad Jani, Siti Nur Diana; Tumijan, Wahidah (Universiti Teknologi MARA, 2023)
Academic life for students was filled with stress and strain. Physical activity, on the other hand, may help people manage their stress levels. Sports students, as all known, are physically active. However, many factors influence perceived academic stress, such as body weight, the semester in question, and gender. The purpose of this study was to investigate the factors that influence perceived academic stress among sports students during online learning. 217 sports students (84=male, 133=female) are involved. The International Physical Activity Questionnaire (IPAQ) - Long Form questionnaire was measured students' level of physical activity participation and the Perception of Academic Stress Scale (PASS) questionnaire used to measure academic stress. Other's variables are measured in demographic profiles. Data were analysed using multiple linear regression to investigate the factors that influence perceived academic stress among sports students during online learning. From the study, 77.40% (n=168) of the students were highly involved in physical activity and the students agreed the perceived academic stress was high for the workload given during online learning, following pressure of perform, academic self-perception and time restraints. The results of the regression indicated the predictor explained 2.6% of the variance (F (1, 215) = 5.73, p=0.018, with an R2 of 0.026). It was found that stay during online learning significantly predicted perceived academic stress (β = .16, p<.001), as did agreeableness (β = -.36, p>=0.018). In conclusion, the data imply that, while many factors influence perceived academic stress, the results in this study were non-significant. Only stay during online learning yielded significant results out of the five parameters indicated.